Perdarahan Kepala Akibat Trauma - Ahmad Roqyal Ain P Putra; Dessy Darmayani Harianja (Pusat Riset dan Inovasi Nasional, 2025)
Traumatology is the study of wounds and injuries and their relationship to violence. One of the major causes of death is head injury, which can cause trauma to both the outer and inner layers of the head. This head injury represents a significant health issue, with approximately 1.7 million people in the United States sustaining a head injury each year. Of this number, more than 52,000 people die, around 275,000 are hospitalized, and nearly 80% receive treatment and are referred to emergency departments. Males experience head injuries more frequently than females. Head trauma is the leading cause of death from trauma, with traffic accidents involving two- and three-wheeled motor vehicles being the most common cause. The primary factors contributing to head injuries are riders not wearing helmets, wearing helmets incorrectly, or using helmets that do not meet safety standards. These accidents often occur when riders fall or are involved in collisions, causing direct impacts to the head. Therefore, it is essential to raise public awareness about wearing helmets correctly and to enforce traffic regulations, especially those related to road safety, in order to reduce the incidence of head injuries and deaths caused by traffic accidents. Prevention through education and safety campaigns is also crucial in efforts to lower accident rates and head injuries.